Social Interaction and Character Education in Islamic Schools - Dwi Ajeng Maulidya Makalao; Mohamad Erihadiana; Asy'ari Asy'ari; Acep Ruskandar (Jurnal Ilmiah Iqra', 2025)
This study aims to analyze how social interactions between students and non-students at Madrasah Tsanawiyah (MTs) Pondok Pesantren Mazro'atul Ulum Citiis contribute to the formation of moral knowing, moral feeling, and moral behavior based on the character education theory formulated by Thomas Lickona. This research uses a qualitative approach. The findings show that inclusive and diverse interactions create learning dynamics that support the development of these three dimensions of character education. The holistic curriculum that integrates religious values and general education plays an important role in shaping students' morals and strengthening their behavior in daily life. The results of this study provide insights into traditional Islamic educational strategies in facing the challenges of modernization while maintaining religious values.